Fiscalité et territoire en France : l’Impôt sur le Revenu des Personnes Physiques (IRPP) - Philippe Waniez (Cybergeo, 2009)
The French Ministry for Finances distributes on its Internet site the results of the collection of the Income tax (IRPP) on a very detailed level, for the 36 500 communes of the country.The direct imposition of the households constituting a source of renewed information each year, and being extremely valuable, one seeks here to evaluate its capacity to express some of the features of the territorial organization of the country. To this end, four elementary indicators were calculated on each commune in order to bring an answer to the following questions: 1° Where does one pay the IRPP, knowing that hardly more than one household out of two pay this tax? 2° Which amount is really paid, measured by the load of imposition viewed as the relationship between the paid tax and the taxable tax income? 3° Which are the differences in average income between the declared wages and the pensions? 4° What is the weight of the pensions in the sum of all incomes?The analysis of a series of thematic maps and a synthesis in the form of a multivariate classification makes it possible to bring new answers to these questions usually put in socio-economic terms and still seldom in geographical terms. These maps visualize marked geographical differences which have a relationship with the economic activities, the urbanization, the migrations… i.e. with the strong structures of French space.